Polaron Rashba effect in an asymmetric quantum dot - Shu-Ping Shan; Shi-Hua Chen; Jing-Lin Xiao (Физика низких температур, 2014)
We study the influence of polaron Rashba effect in an asymmetric quantum dot. Using variational method, we derive the expression of the polaron ground state energy. We also discuss the dependencies of the ground state energy on the wave vector and the transverse (longitudinal) effective confinement length. It is found that the ground state energy splits into two branches due to the Rashba effect. The spin splitting energy is an increasing function of the wave vector and the Rashba SO parameter.